Zasoby ludzkie jako kluczowy czynnik rozwoju przedsiębiorstwa - Zając, Czesław (Human Resources as a Factor of the Companies Development, 2008)
Human resources are regarded more often as an important factor of the development of contemporary enterprises. The quality of these resources, including their competences, decides in a big scale about possibilities of strategic objectives fulfillment. This thesis has been proved on the basis of resource theory of the firm and strategic management. Such features of human resources like specificity, complexity, high capability of change, low ability of substitution in the field of management and scarcity have been described in this paper. It is underlined that companies can build and broad their competences at the same time, increasing in this way their core competences. They obtain additionally strategic synergy. Linking human resources with competences empowers activities which are overcoming limits of human resources management standards and generates a necessity of strategic human resources management. It also forces to treat organizational culture as a "special resource". The appropriate shaping of this resource becomes a key factor of strategic adjustment of companies to their environment. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 34, s. 89-97